Examining the effects of social and cash transfer programs for homeless adults: Evidence from the Samaritan pilot - Andrew Wright; Donghoon Lee; Arisa Marshall; Layla G. Booshehri; Jerome A. Dugan (Elsevier, 2022)
Objective: To conduct a program evaluation of a technology-based intervention for a housing insecure population. Study design: We conduct a quantitative analysis of Samaritan pilot administrative records. Methods: Samaritan conducted an initial single-arm pilot of their technology platform among a housing insecure population (N = 500). Administrative records containing basic demographics and social determinants of health were analyzed as part of this evaluation. Results: Our analysis revealed that among the participants, roughly 60% reported one or more improvements in unmet social determinants of health, showing the greatest improvements in the areas of utilities and nutrition. A gender subgroup analysis also revealed a differential pattern of platform use to address social determinant needs, with women more likely to report improvements in housing and nutrition while men report improvements in income and hope categories. Conclusion: Samaritan, a technology-based intervention targeted at housing insecure individuals, aims to connect users to the financial and social capital necessary to improve their current situations. The results of the pilot demonstrate the potential role the Samaritan platform could play in addressing social determinant needs and insights on potentially useful technology-based intervention features for housing insecure populations.